ZAKAT AND POVERTY ALLEVIATION IN INDONESIA: A PANEL ANALYSIS AT PROVINCIAL LEVEL - Evi Aninatin Ni'matul Choiriyah; Abdul Kafi; Irma Faikhotul Hikmah; Imam Wahyudi Indrawan (Bank Indonesia, 2020)
As a pillar of Islam and an instrument for poverty alleviation, zakat is perceived as an effective tool for tackling the problem of poverty in the Muslim world. However, whether zakat is effective in improving indicators of both quantity and quality of poverty is still a question requiring empirical investigation. This study is aims to empirically investigate the role of impactful zakat in poverty alleviation as indicated by the BAZNAS prosperity index (Indeks Kesejahteraan BAZNAS or IKB), at provincial level in Indonesia. This study covers annual data from 28 provinces in Indonesia for the years 2017 and 2018. Data analysis uses a panel-data approach, with three indicators of poverty – the poverty headcount ratio (P0), poverty gap index (P1), and poverty severity index (P2) – as dependent variables. The study finds that higher BAZNAS IKB, used as a sign of impactful zakat, significantly reduces P0 but has insignificant effect on P1 and P2. The results of this study imply that zakat managers should put emphasis on the poorest section of the poor population to enable improvements in poverty indicators through zakat utilization.